Orthostatic Hypotension in Elderly Patients with Essential Tremor - Kaya D; Aydin AE; Isik AT (Clinical Interventions in Aging, 2021)
Derya Kaya,1 Ali Ekrem Aydin,2 Ahmet Turan Isik1 1Unit for Brain Aging and Dementia, Department of Geriatric Medicine, Faculty of Medicine, Dokuz Eylül University, Izmir, Turkey; 2Department of Geriatric Medicine, Sivas State Hospital, Sivas, TurkeyCorrespondence: Derya KayaUnit for Brain Aging and Dementia, Department of Geriatric Medicine, Faculty of Medicine, Dokuz Eylül University, Balçova, Izmir 35340, TurkeyTel +90 232 412 43 41Fax +90 232 412 43 39Email deryakaya29@gmail.comPurpose: Essential tremor (ET) is the most common movement disorder in which dysautonomia symptoms can be present. We aimed to evaluate the presence of orthostatic hypotension (OH) and its relationship with the clinical features.Patients and Methods: Forty-four elderly patients with ET and 118 healthy elderly controls were included. OH was assessed via the head-up tilt table test and defined, according to the change in position, as a drop of at least 20 mmHg in systolic blood pressure and/or 10 mmHg in diastolic blood pressure. Tremor severity was evaluated using the Fahn-Tolosa-Marin Tremor Rating (FTMTR) Scale. All patients underwent geriatric comprehensive assessment.Results: There were no differences between the controls and patients with ET regarding age and gender. The mean age was 72.8± 6.1, the mean disease duration 19.1± 13.5 years and the mean FTMTR score was 30.9± 17.1 in patients with ET. The frequency of OH at the 1st minute in patients with ET was higher than in controls (31.8% vs 17.8%, p=0.046). Furthermore, the frequency of jaw tremor in patients with OH was higher than in those without OH (35.7% vs 6.7%, p=0.025). About 28.6% of ET patients with OH had orthostatic symptoms.Conclusion: We demonstrated that ET patients, particularly those with jaw tremors, had OH and that most of them were asymptomatic. Therefore, in order to protect patients from complications related to OH, it would be appropriate to evaluate OH in the follow-up and treatment of elderly patients with ET.Keywords: essential tremor, orthostatic hypotension, head-up tilt table test, jaw tremor, elderly